Ihya al-Lughah as Arabic Language Learning Model to Improve Arabic Speaking Skills - Kosim, Nanang; Maryani, Novy (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
Arabic language learning in Sukahideng Islamic boarding school experiences several obstacles, such as students feeling bored and tired to learn to speak Arabic because teachers tend to dominate learning activities in the classroom compared to students. Thus, the application of a model that improves learning is needed because it is one of the tools to achieve goals. This research aims to produce a product in the form of a learning model to improve Arabic language skills through the Ihya al-Lughah Learning Model. The method used in this research is Research and Development (R&D) with experimental method. Data collection was done through observation techniques. Interviews were conducted with students, teachers, and boarding school leaders. Documentation was done by looking at various data in the field. Data analysis was done inductively. The research stages include preliminary studies, development, and validation. Based on the fifth point, the research findings at Sukahideng Islamic boarding school show that the application of the Ihya al-Lughah model is more effective than conventional Arabic learning. This effectiveness is indicated by the difference in test results between the experimental santri group (the group that received treatment using the learning model developed in this study) and the control santri group (the group that did not receive treatment using the learning model). This research is expected to contribute and become one of the effective and efficient learning models in Arabic language learning, as well as useful for readers and Arabic language activists to apply it in Arabic language learning.